Kolaborasi Guru dan Manajemen Sekolah dalam Pengembangan Kurikulum Efektif - Muti Atus Sofiah; Rahma Nanda Nur Azizah; Luat happyana (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to identify the role of collaboration between teachers and school management in developing an effective curriculum at SMP Plus Darussalam. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews with school principals, teachers and students, as well as participatory observation and analysis of documents related to the curriculum. The research results reveal that close collaboration between teachers and school management is very important in designing and implementing a curriculum that suits students' needs. Collaborative involvement with various parties enriches the curriculum development process, increases the relevance of the material, and facilitates responsive adjustments to educational challenges. This research concludes that a collaborative approach not only improves curriculum quality but also increases teacher satisfaction and student motivation. The implication of these findings is the need to integrate collaborative models in curriculum development in other schools to achieve more adaptive and effective education, as well as strengthen a supportive and inclusive learning environment.